(untitled) (Филологические заметки, 2019)
The text dealt with the psychological explanation of the phenomenon of empathy as a base in the contribution towards developing the notion of care for other people. Empathy, provided it coincides with moral principles, may play an important role in moral reasoning. We believe that literature affects morality, since it is by reading that one strengthens the ability to enter into another person’s individualised life. In the present text we have taken over, promoted and developed the thesis by Martha Nussbaum that „literary understanding develops habits of the mind that lead towards social equality by contributing towards the abolishment of stereotypes that support collective hatred“. (Nussbaum 2005: 125) For the research in this text the role of the character is important in sabotaging stereotypes and generalisations. This is important regardless of the fact whether characters of different nationalities help each other, or the story is about one character who opposes the nationalism of his own group, or the fact that characters who are suffering belong to different nationalities. The published article is part of a wider research that analyses war prose from empathetic and ethical aspect.